1891 W. Va. Code 915–16, ch. 148, § 7 - (:unkn) unknown (General Publisher, 1891)
If a person carry about his person any revolver or other pistol, dirk, bowie knife, razor, slung shot, billy, metallic or other false knuckles, or any other dangerous or deadly weapon of like kind or character, he shall be guilty of a misdemeanor, and fined not less than twenty-five nor more than two hundred dollars, and may, at the discretion of the court, be confined in jail not less than one nor more than twelve months; and if any person shall sell or furnish any such weapon as is hereinbefore mentioned to a person whom he knows, or has reason, from his appearance or otherwise, to believe to be under the age of twenty-one years, he shall be punished as hereinbefore provided
--
Keywords: CARRY; TRANSFER - MINORS